On Some Forms of “Out-Group” Intolerance and “Unlimited” Tolerance in Linguoculture - Harutyunyan, Narine (Armenian Folia Anglistika, 2019)
The subject of the research is ethnic intolerance as a form of relationship between “we” and “other”, manifested in various modifications of the hostility towards others. There are several main types of ethno-intolerant relations: ethnocentrism; xenophobia, migrant phobia, etc. The author’s definitions of such concepts as “intercultural whirlpool”, “ethnocentric craters” and “xenophobic craters”, “emotional turbulence of communication” are presented. The negative, discreditable signs of ethnicity of a particular national community are represented in the lexical units of English in such a way as if the “other” ethnic group has the shortcomings that are not in the “we” group. The problem of “unlimited” tolerance is considered when “strangers” – immigrants, seek to impose “their own” religious and cultural traditions, worldview and psychological dominant on local people. The article deals with the problems of intolerance and “unlimited” tolerance not only as complex socio-psychological, but also as linguocultural phenomena that are actualized in the linguistic consciousness of the ethnic group (English-speaking groups, in particular). The article also deals with the problem of “aggressive” expansion of the English language, which destroys the nation’s value system, distorts its language habits and perception of the surrounding reality, and creates discriminatory dominance of a certain linguoculture.